2020
DOI: 10.1136/bcr-2019-231995
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of the pregnant patient in haemorrhagic shock secondary to an undiagnosed ruptured liver adenoma

Abstract: Management of a ruptured hepatocellular adenoma during pregnancy is a rare and potentially life-threatening entity. Few case reports have described management of the pregnant patient who presents in haemorrhagic shock secondary to a ruptured liver adenoma. A 30-year-old primigravid woman at 31 weeks pregnant presented with abdominal pain and fetal bradycardia. After stat caesarean delivery of the infant, she had continued hemoperitoneum and was in shock secondary to an undiagnosed ruptured liver mass. General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Fifteen cases of HCA-associated hemorrhage were included, none occurred in the first trimester and all HCA measuring 6.5 cm. 33,34,36,43,44,46,49,52 Eight HCA bled during gestation, seven in the third trimester. The remaining seven bleeding cases occurred during labor (n = 2) or postpartum (n = 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen cases of HCA-associated hemorrhage were included, none occurred in the first trimester and all HCA measuring 6.5 cm. 33,34,36,43,44,46,49,52 Eight HCA bled during gestation, seven in the third trimester. The remaining seven bleeding cases occurred during labor (n = 2) or postpartum (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…11, OCP status was reported in most studies (79%). 26,28,30,[42][43][44][45]52 Four cohort studies reported insufficient information on patient characteristics, HCA size, and HCA behavior for reporting and pooling of individual patients. 3,[54][55][56] One case report and one cohort study reported on hepatocyte nuclear factor 1a maturity onset diabetes of the young (HNF1A-MODY)-associated HCA.…”
Section: Data Extraction and Critical Appraisalmentioning
confidence: 99%
“…However, it has been documented. In a recent case report, a 30-year-old primigravid was managed with temporary packing and definitive control of hemorrhage via angioembolization of a bleeding HCA [ 7 ]. This case report highlighted the importance of a multidisciplinary approach in managing this rare, but life-threatening condition.…”
Section: Introductionmentioning
confidence: 99%